The source and market development of a premium product – Beef from the Argentine Pampas - Champredonde, Marcelo (Elsevier, 2019)
The two main features of beef from the Argentine Pampas are its quality and geographical origin. In addition to the normal aspects of meat quality detected by sensory panels or measured by scientific instruments, the quality of Pampean beef includes the powerful symbolic quality of pampas life – the immensity of the green grasslands and the culture of the gaucho, living on horseback or sipping mate while making an asado (barbecue). This review defines the qualities and geographical origin of Pampean beef, and explains their interrelationships in terms of animal breed, nutrition and production systems. The objective is to help secure Pampean beef against unfair encroachment from competing products which lack the true authenticity of beef from the Argentine Pampas.